Plasma miR-199a-5p is increased in neutrophilic phenotype asthma patients and negatively correlated with pulmonary function - Huang, Yali; Zhang, Shengding; Fang, Xiaoyu; Qin, Lu; Fan, Yu; Ding, Dandan; Liu, Xiansheng; Xie, Min (PloS one, 2018)
We investigated the relationship between plasma miRNAs levels and inflammatory characteristics in asthmatic patients. Eligible adults with untreated asthma (n = 35) underwent a clinical assessment, sputum induction, and assessment of pulmonary function test and Asthma Control Test (ACT) scores. Asthma phenotypes were defined using the sputum cell count. miR-199a-5p expression was measured using quantitative real-time polymerase chain reaction (qPCR). Lipopolysaccharide (LPS) stimulation was used to detect miR-199a-5p secretion from peripheral blood-derived neutrophil, lymphocyte, macrophage and BEAS-2B cells. The correlation of miR-199a-5p expression with clinical parameters was analyzed using multiple linear regression analysis. In silico analysis predicted the target genes and signaling pathway of miR-199a-5p. Transfection of miR-199a-5p mimics in human airway smooth muscle cells (HASMCs) was performed in vitro. The miRNA-199a-5p levels in plasma and sputum increased significantly in patients with neutrophilic asthma compared to healthy subjects (ps = 0.014 and 0.006, respectively). Expression of miR-199a-5p in the plasma of asthmatic patients positively correlated with sputum miR-199a-5p expression (r = 0.511, p = 0.021). The miR-199a-5p level was only elevated with LPS stimulation in neutrophils but not macrophages, lymphocytes, or epithelial cells from healthy controls (p < 0.01). miR-199a-5p expression increased in response to LPS (p = 0.005) and LPS combined with IL-4 (p = 0.003), but not IL-4 alone. However, peripheral neutrophils from eosinophilic asthma patients did not respond to LPS with increased miR-199a-5p expression (n = 5, p > 0.05) in contrast to the significant response from neutrophilic patients (n = 4, p < 0.0001). miR-199a-5p negatively correlated with FEV1, FVC and PEF (r = -0.377, p = 0.026; r = -0.419, p = 0.012; and r = -0.392, p = 0.024, respectively). Multivariate correlation analysis confirmed that the plasma miR-199a-5p levels negatively correlated with FEV1 in patients with asthma (Adjusted R2 = 0.164, p = 0.015). In silico analysis suggested that the WNT signaling pathway participates in miR-199a-5p mediation of smooth muscle cell hypertrophy. In vitro experiment, miR-199a-5p mimics inhibited the protein expressions of WNT2 and WNT4, decreased the c-myc expression and dramatically increased the Sm-MHC expression in HASMCs. Plasma miR-199a-5p was increased in neutrophilic asthma and negatively correlated with pulmonary function, which suggests that miR-199a-5p actively contributes to disease pathogenesis by modulating the inflammatory process and transferring the signal from inflammatory cells to structure cells.